Hard gains through soft contracts: productive engagement of private providers in tuberculosis control - Knut Lönnroth; Mukund Uplekar; Léopold Blanc (The World Health Organization, 2006)
Over the past decade, there has been a rapid increase in the number of initiatives involving "for-profit" private health care providers in national tuberculosis (TB) control efforts. We reviewed 15 such initiatives with respect to contractual arrangements, quality of care and success achieved in TB control. In seven initiatives, the National TB Programme (NTP) interacted directly with for-profit providers; while in the remaining eight, the NTP collaborated with for-profit providers through intermediary not-for-profit nongovernmental organizations. All but one of the initiatives used relational "drugs-for-performance contracts" to engage for-profit providers, i.e. drugs were provided free of charge by the NTP emphasizing that providers dispense them free of charge to patients and follow national guidelines for diagnosis and treatment. We found that 90% (range 61-96%) of new smear-positive pulmonary TB cases were successfully treated across all initiatives and TB case detection rates increased between 10% and 36%. We conclude that for-profit providers can be effectively involved in TB control through informal, but well defined drugs-for-performance contracts. The contracting party should be able to reach a common understanding concerning goals and role division with for-profit providers and monitor them for content and quality. Relational drugs-for-performance contracts minimize the need for handling the legal and financial aspects of classical contracting. We opine that further analysis is required to assess if such "soft" contracts are sufficient to scale up private for-profit provider involvement in TB control and other priority health interventions.